Review of technologies for monitoring the performance of marine structures - Votsis, Renos; Michailides, Constantine; Tantele, Elia; Onoufriou, Toula (My University, 2018)
A huge number of marine (coastal and offshore) structures of different types, floating or fixed, and of various sizes have been constructed and installed worldwide. The state of a marine structure during its life cycle must remain in the domain specified in design, although this can be altered by normal aging due to usage, by the action of the environment, and by accidental events. In recent years the field of smart technologies (structural and environmental monitoring), including sensing and control, has been growing at a fast rate. The selection of an effective method for observing the marine structure's performance and integrity, as well as their control is of paramount importance aiming to give a diagnosis of the 'health' of the examined marine structure In the present paper an insight into the monitoring technologies that exist for observing the performance of marine structures is presented. Critical information on monitoring marine structures with regard to the existing technologies, the measured quantities and applications on different types of marine structures, that are used in both offshore (e.g. oil and gas structures and systems, offshore renewables) and coastal (e.g. jetties, pipelines, breakwaters) areas are presented and discussed.
Keywords: Accelerations; Acoustic emission; Marine structures; Strains; Structural health monitoring